Guest‐Assisted Proton Conduction in the Sulfonic Mesoporous MIL‐101 MOF. Issue 20 (26th June 2019) - Devautour‐Vinot, Sabine; Sanil, Eriyakkadan S.; Geneste, Amine; Ortiz, Vanessa; Yot, Pascal G.; Chang, Jong‐San; Maurin, Guillaume
Abstract: Post‐synthesis modification of MIL‐101(Cr)‐NO2 was explored in order to decorate the organic backbone by propyl‐sulfonic groups, with the aim to incorporate mobile and acidic protons for solid‐state proton electrolyte applications. The resulting solid switched from insulating towards proton superconductive behavior under humidity, while the conductivity recorded at 363 K and 95 % relative humidity reached 4.8×10 −3  S cm −1 . Propitiously, the impregnation of the material by strong acidic molecules (H2 SO4 ) further boosted the proton conductivity performances up to the remarkable σ value of 1.3×10 −1  S cm −1 at 363 K/95 % RH, which reaches the performances of the best proton conductive MOF reported so far. Abstract : Propyl‐sulfonic groups were incorporated into MIL‐101(Cr)‐NO2 to generate a proton conductive metal–organic framework, whose remarkable performance ( σ =1.3×10 −1  S cm −1 at 363 K/95 % RH) was strongly enhanced by H2 O/H2 SO4 impregnation.